Optimization Of Collimator Design For Bnct Based Cyclotron 30 Mev And Its Dosimetry Simulation In Head And Neck Soft Tissue Sarcoma Using Monte Carlo N Particle X Program - Ardana, I Made (2015)
Abstract This article involves two main objectives for BNCT system. First goal includes optimization of cyclotron based BNCT collimator. Second goal is to calculate the neutron flux and dosimetry system of Boron Neutron Capture Therapy (BNCT) in head and neck soft tissue sarcoma (STS). A series of simulations has been carried out using a Monte Carlo N Particle X program to find out the final composition and configuration of a collimator to moderate the fast neutron flux which is generated from the thick beryllium target. The final configuration for collimator design included 39 cm aluminium as moderator, 8.2 cm lithium fluoride as fast neutron filter and 0.5 cm boron carbide as thermal neutron filter. Bismuth, lead fluoride, and lead were chosen as the aperture, reflector, and gamma shielding, respectively. Epithermal neutron fluxes in the suggested design were 2.83E9 n/cm2 s, while other IAEA parameters for BNCT collimator design had been satisfied. In the next step, it was simulated its dosimetry for head and neck soft tissue sarcoma. Simulations carried out by varying the concentration of boron compounds in ORNL neck phantom model to obtained the optimal dosimetry results. MCNPX calculation showed that the optimal depth for thermal neutron was 4.8 cm in tissue phantom with the maximum dose rate was in GTV on each boron concentration variation respectively. The irradiated time needed for this therapy for each variables respectively less than an hour.